Сучасні аспекти діагностики та лікування вузлових форм зоба - Tarashchenko, Yu.M.; Kovalenko, A.Ye.; Bolgov, M.Yu. (Ендокринологія | Endokrynologia, 2020)
Сучасні аспекти діагностики та лікування вузлових форм зоба